PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PASIEN TERHADAP LOYALITAS PASIEN RAWAT JALAN DAN RAWAT INAP DI RUMAH SAKIT EMBUNG FATIMAH BATAM - Muhammad Ibnu Fajar; Rahman Hasibuan (EQUILIBIRIA, 2016)
In this study, entitled "the influence of the quality of service and the satisfaction of Patients Against the loyalty of Outpatient And inpatient care in a hospital Fatimah Batam Dam", the authors examine whether there is a positive relationship between quality services and loyalty satisfaction with outpatient and inpatient care in hospitals dam Fatimah batam.The purpose of this research is to know the quality of service: outpatient and hospitalization in hospital apply dam Fatimah batam, satisfaction of patients against hospital loyalty dam Fatimah batam, and a huge influence on the quality of service and the satisfaction of patients against the loyalty of outpatient and inpatient hospital dam Fatimah batam.The methods used in this research is qualitative and quantitative methods. Method of sampling in this research is with the method of proportionate stratified random sampling. With population size (N) = 163, then the number of patients who will be calculated using the formula respondents Slovin (Umar, 2010) number of respondents to this study with an error rate of 10% (confidence level of 90%) are 65 respondents.